In vivo imaging reveals rapid astrocyte depletion and axon damage in a model of neuromyelitis optica‐related pathology - Herwerth, Marina (Ann Neurol, 2016)
OBJECTIVE: Neuromyelitis optica (NMO) is an autoimmune disease of the central nervous system, which resembles multiple sclerosis (MS). NMO differs from MS, however, in the distribution and histology of neuroinflammatory lesions and shows a more aggressive clinical course. Moreover, the majority of NMO patients carry immunoglobulin G autoantibodies against aquaporin‐4 (AQP4), an astrocytic water channel. Antibodies against AQP4 can damage astrocytes by complement, but NMO histopathology also shows demyelination, and — importantly—axon injury, which may determine permanent deficits following NMO relapses. The dynamics of astrocyte injury in NMO and the mechanisms by which toxicity spreads to axons are not understood. METHODS: Here, we establish in vivo imaging of the spinal cord, one of the main sites of NMO pathology, as a powerful tool to study the formation of experimental NMO‐related lesions caused by human AQP4 antibodies in mice. RESULTS: We found that human AQP4 antibodies caused acute astrocyte depletion with initial oligodendrocyte survival. Within 2 hours of antibody application, we observed secondary axon injury in the form of progressive swellings. Astrocyte toxicity and axon damage were dependent on AQP4 antibody titer and complement, specifically C1q. INTERPRETATION: In vivo imaging of the spinal cord reveals the swift development of NMO‐related acute axon injury after AQP4 antibody‐mediated astrocyte depletion. This approach will be useful in studying the mechanisms underlying the spread of NMO pathology beyond astrocytes, as well as in evaluating potential neuroprotective interventions. Ann Neurol 2016;79:794–805